The minimum reflux ratio manifolds for the case of chloroform–benzene–toluene mixture rectification in the mode of the first class fractionalization - K. Yu. Tarkhov; L. A. Serafimov; A. M. Andreeva (Тонкие химические технологии)
Using modern methods of mathematical modeling the minimum reflux ratio values were calculated for the wide range of initial compositions for the zeotropic chloroform-benzene-toluene mixture in the absence of α=1 manifolds and for the case of rectification in the mode of the first class fractionalization. The form, shape and location of minimum reflux ration lines are represented on the diagram for the considered mixture and conditions. Some analytical and graphical peculiarities and regularities were revealed in the course of the calculation.